Determinants of Tax Avoidance: Examining the Roles of Capital Intensity, Business Ethics, and Financial Distress with Political Connections as a Moderating Factor - Ema Melinda; Trisni Suryarini (Universitas Ibn Khladun Bogor, 2026)
Tax avoidance is a strategy employed by companies to minimize tax burdens; however, such practices may generate various implications for both firms and governments. Factors such as capital intensity, business ethics, and financial distress are considered potential determinants of tax avoidance. In addition, political connection may strengthen or weaken the relationship between these factors and tax avoidance. This study aims to examine the effects of capital intensity, business ethics, and financial distress on tax avoidance, with political connection serving as a moderating variable. The study utilizes secondary data obtained from basic materials sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The sample was selected using purposive sampling, resulting in 108 observations. Data were analyzed using panel data regression with EViews 13 software. The findings indicate that capital intensity and financial distress have no significant effect on tax avoidance, while business ethics has a negative effect on tax avoidance. Furthermore, political connection strengthens the effect of capital intensity on tax avoidance but does not moderate the relationships between business ethics, financial distress, and tax avoidance.